2001
DOI: 10.1034/j.1399-3054.2001.1110201.x
|View full text |Cite
|
Sign up to set email alerts
|

Fruit size: Towards an understanding of the metabolic control of fruit growth using avocado as a model system

Abstract: Final fruit size is the consequence of complex metabolic events of final fruit size by cell division is 3-hydroxy-3-methylglutaryl coenzyme A reductase (HMGR) and activity of the sucrose that occur between fruit set and maturation. Disruption of these non-fermenting 1-related protein kinase (SnRK1) complex. It biochemical and molecular processes at any stage during fruit growth will impact on final fruit size. Because fruit size is a is argued that sugar content and composition of sink cells impact on SnRK1 (a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
1
2

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 84 publications
1
35
1
2
Order By: Relevance
“…In order to increase the size of some organs and tissues, there are two possible methods, to increase cell numbers or cell size. Several reports have shown that the final fruit size is related to the number of cells, not to cell size (Cowan et al, 2001;Higashi et al, 1999;Zhang et al, 2006). In the present study, however, microscopic observation revealed that the cell size of the pericarp tissues of C. annuum 'Oh-natsume' was larger than that of C. annuum 'Shishitou No.…”
Section: Degree Of Polysomaty In Pericarp Cells Of Mature Fruitscontrasting
confidence: 52%
“…In order to increase the size of some organs and tissues, there are two possible methods, to increase cell numbers or cell size. Several reports have shown that the final fruit size is related to the number of cells, not to cell size (Cowan et al, 2001;Higashi et al, 1999;Zhang et al, 2006). In the present study, however, microscopic observation revealed that the cell size of the pericarp tissues of C. annuum 'Oh-natsume' was larger than that of C. annuum 'Shishitou No.…”
Section: Degree Of Polysomaty In Pericarp Cells Of Mature Fruitscontrasting
confidence: 52%
“…Soluble sugars are, however, not the only components in the large regulatory network that exists within seed tissues and aects their interactions (see e.g. Weber 1999, for seeds, andCowan et al 2001, for fruits). Most probably the activity of this regulatory network will also be re¯ected by the expression pattern of genes at the mRNA level.…”
Section: Introductionmentioning
confidence: 99%
“…But excessive shoot growth reduces fruit size fruit quality and yield due to antagonism from leafproduced assimilates (Cowan et al, 2001). The cultivar CO-2 is a dual-purpose cultivar suited both for use as greens and for production of grains.…”
Section: Introductionmentioning
confidence: 99%